2019
DOI: 10.15585/mmwr.ss6807a1
|View full text |Cite
|
Sign up to set email alerts
|

Surveillance for Coccidioidomycosis — United States, 2011–2017

Abstract: Problem/ConditionCoccidioidomycosis (Valley fever) is an infection caused by the environmental fungus Coccidioides spp., which typically causes respiratory illness but also can lead to disseminated disease. This fungus typically lives in soils in warm, arid regions, including the southwestern United States.Reporting Period2011–2017.Description of SystemCoccidioidomycosis has been nationally notifiable since 1995 and is reportable in 26 states and the District of Columbia (DC), where laboratories and physicians… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
50
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 15 publications
4
50
2
4
Order By: Relevance
“…Previous analyses show that coccidioidomycosis awareness is high in Arizona (97%) (4) and lower in California (42%) (California Department of Public Health, unpublished data, 2020). More than 95% of cases occur in these two states, with most cases concentrated in Arizona's Sonoran Desert and California's southern San Joaquin Valley (5). The results suggest much lower levels of awareness in the West (of which Arizona and California account for 87% of the population) than previous studies (4,5), possibly because of methodologic differences.…”
Section: Discussioncontrasting
confidence: 49%
See 1 more Smart Citation
“…Previous analyses show that coccidioidomycosis awareness is high in Arizona (97%) (4) and lower in California (42%) (California Department of Public Health, unpublished data, 2020). More than 95% of cases occur in these two states, with most cases concentrated in Arizona's Sonoran Desert and California's southern San Joaquin Valley (5). The results suggest much lower levels of awareness in the West (of which Arizona and California account for 87% of the population) than previous studies (4,5), possibly because of methodologic differences.…”
Section: Discussioncontrasting
confidence: 49%
“…More than 95% of cases occur in these two states, with most cases concentrated in Arizona's Sonoran Desert and California's southern San Joaquin Valley (5). The results suggest much lower levels of awareness in the West (of which Arizona and California account for 87% of the population) than previous studies (4,5), possibly because of methodologic differences. The lower awareness of coccidioidomycosis among non-White and multiracial respondents is noteworthy given that Black race and Filipino ethnicity are risk factors for severe or disseminated disease.…”
Section: Discussioncontrasting
confidence: 49%
“…Coccidioides is endemic in regions with heavy intermittent rains along with the hot, arid summers (Johnson et al, 2014;Coopersmith et al, 2017;McCotter et al, 2019) It is found primarily in alkaline soils with high surface salinity (Elconin et al, 1964;Swatek, 1970;Lacy and Swatek, 1974). During wet, rainy months, filamentous threads composed of barrel-like subunits called arthroconidia expand within the soil.…”
Section: Disease and Epidemiologymentioning
confidence: 99%
“…During wet, rainy months, filamentous threads composed of barrel-like subunits called arthroconidia expand within the soil. Environmental stresses, such as heat or digging, disrupts the soil and aerosolize the arthroconidia, making it airborne (McCotter et al, 2019). Infection occurs when arthroconidia are inhaled into the lungs and temperature and moisture differences trigger morphological change from arthroconidia to spherule to endospore (Johannesson et al, 2006).…”
Section: Disease and Epidemiologymentioning
confidence: 99%
“…Coccidioidomycosis is an infection caused by dimorphic fungi of the genus Coccidioides ( C immitis and C posadasii ). C immitis is endemic to the south‐western United States (US), primarily the state of California, with the highest incidence in California's Central Valley; C immitis is also found in Nevada, New Mexico, Utah, increasingly in previously non‐endemic parts of the United States such as Washington State, 1,2 as well as parts of Baja California, Mexico 3 . C posadasii is endemic in parts of the United States including southern California, 4 Nevada, Arizona, New Mexico and Texas, 3 as well as parts of Mexico, Central and South America 1,5 …”
Section: Introductionmentioning
confidence: 99%